Consecutive reactions to construct tricarbonyl compounds and synthetic applications thereof. Issue 53 (11th October 2021) - Madroñero, Diego; Mujica-Martinez, Cesar A.; Vázquez, Alfredo
Abstract : A cascade process to construct synthetically valuable β-keto-β′-acylcycloalkanecarboxylic acid esters and their transformation into bicyclic and tricyclic systems through intramolecular condensation reactions. Abstract : Lithium anions derived from O-carbonate-protected cyanohydrins undergo conjugate addition to cycloalkenones with the concomitant transfer of the alkoxycarbonyl group to produce tricarbonyl compounds. These products offer numerous possibilities for further elaboration. The synthetic potential of the cascade products was demonstrated by forming bicyclic and tricyclic systems through intramolecular condensation reactions.